Skeletal Muscle Loss During Treatment With Abiraterone in Patients With Metastatic Prostate Cancer - Eva Streckova; Jiri Stejskal; Daniela Kuruczova; Adam Svobodnik; Radka Stepanova; Tomas Buchler (Prostate Cancer)
Conclusions: SMI decline occurs during AAP treatment for mHSPC and mCRPC, and is more pronounced in patients over 75 years old and those without previous local treatment. There was no statistically significant association between survival outcomes and SMI decline during AAP therapy.